2019
DOI: 10.1016/j.pmedr.2019.100966
|View full text |Cite
|
Sign up to set email alerts
|

Baseline assessment of noticing e-cigarette health warnings among youth and young adults in the United States, Canada and England, and associations with harm perceptions, nicotine awareness and warning recall

Abstract: Health warnings on tobacco products can inform users of potential risks. However, little is known about young people's exposure to health warnings on e-cigarette products. This baseline assessment of young people's noticing e-cigarette warnings uses nationally representative data from three countries. Data were collected under Wave 1 of the ITC Youth Tobacco and E-cigarette Survey, conducted in Canada, England, and the US. Online surveys were completed by 16–19-year-olds in July/August 2017 ( … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
15
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 20 publications
3
15
1
Order By: Relevance
“…In addition, we examined the associations between both harm perception measures and our three e-cigarette use intention measures with Pearson’s correlation tests. Based on previous research with young adults finding e-cigarette harm perception differences by user groups [ 14 ], current study results are presented for participants overall and by four mutually exclusive user categories—nonusers (who neither smoke nor vape), current exclusive cigarette smokers (i.e., currently smoke cigarettes “some days” or “every day” but do not currently use e-cigarettes), current exclusive e-cigarette users (i.e., currently vape “some days” or “every day” but do not currently smoke cigarettes), and dual users (i.e., participants who report both smoking and vaping “some days” or “every day”).…”
Section: Methodsmentioning
confidence: 99%
“…In addition, we examined the associations between both harm perception measures and our three e-cigarette use intention measures with Pearson’s correlation tests. Based on previous research with young adults finding e-cigarette harm perception differences by user groups [ 14 ], current study results are presented for participants overall and by four mutually exclusive user categories—nonusers (who neither smoke nor vape), current exclusive cigarette smokers (i.e., currently smoke cigarettes “some days” or “every day” but do not currently use e-cigarettes), current exclusive e-cigarette users (i.e., currently vape “some days” or “every day” but do not currently smoke cigarettes), and dual users (i.e., participants who report both smoking and vaping “some days” or “every day”).…”
Section: Methodsmentioning
confidence: 99%
“…After viewing the advertisement for at least 10 seconds, participants responded to three items about the advertisement (advertisement appeal, product appeal, likelihood of purchasing) ( Stark et al, 2008 ). After viewing both advertisements, participants responded to items about the warning and about e-cigarette beliefs about addiction or harm and use intentions ( Sontag et al, 2019 , Mays et al, 2016 ). Items about the warning included attention ( King et al, 2020 ), recall ( King et al, 2020 , Strasser et al, 2012 ), clarity, cognition (how much the warning made participants think about the health risks of vaping) ( Hammond et al, 2007 ), perceived knowledge gained ( Magnan and Cameron, 2015 ), perceived message effectiveness (extent to which participants perceived the message made e-cigarettes seem unpleasant, discouraged their interest in e-cigarettes, and made them more concerned about health effects) ( Noar et al, 2016 ), likelihood to share with friends ( Morgan et al, 2018 ), psychological reactance (extent to which the warning was perceived as being overblown, manipulative, and annoying) ( Hall et al, 2018 ), and negative affect (extent to which the warning evoked emotional reactions including feeling scared, regretful, on edge, disgusted, sad) ( Hall et al, 2018 ).…”
Section: Methodsmentioning
confidence: 99%
“…Other studies found that current adult smokers (versus never/former smokers) were more likely to perceive lower relative harms of e-cigarettes versus cigarettes [13,16,26]. Further, both cigarette and dual (e-cigarette and cigarette) users hold lower absolute harms perceptions of e-cigarettes, relative to non-users of either product [27]. A direct comparison of absolute and relative harm perception measures found that, regardless of smoking status, participants were more likely to perceive e-cigarettes as less harmful than cigarettes when answering absolute versus relative measures of harm [28].…”
Section: Introductionmentioning
confidence: 97%